2005
DOI: 10.1021/bi051357o
|View full text |Cite
|
Sign up to set email alerts
|

Peptergents:  Peptide Detergents That Improve Stability and Functionality of a Membrane Protein, Glycerol-3-phosphate Dehydrogenase

Abstract: Toward enhancing in vitro membrane protein studies, we have utilized small self-assembling peptides with detergent properties ("peptergents") to extract and stabilize the integral membrane flavoenzyme, glycerol-3-phosphate dehydrogenase (GlpD), and the soluble redox flavoenzyme, NADH peroxidase (Npx). GlpD is a six transmembrane spanning redox enzyme that catalyzes the oxidation of glycerol-3-phosphate to dihydroxyacetone phosphate. Although detergents such as n-octyl--D-glucpyranoside can efficiently solubili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 26 publications
(45 reference statements)
3
74
0
Order By: Relevance
“…GlpD was expressed, detergent extracted, purified, and assayed as published (40). As detailed in the earlier report, detergent screening to maintain the activity of GlpD was conducted; for the structural and biochemical studies reported here, 1-O-noctyl-␤-D-glucopyranoside (␤-OG; MW 292.4) was used as the detergent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GlpD was expressed, detergent extracted, purified, and assayed as published (40). As detailed in the earlier report, detergent screening to maintain the activity of GlpD was conducted; for the structural and biochemical studies reported here, 1-O-noctyl-␤-D-glucopyranoside (␤-OG; MW 292.4) was used as the detergent.…”
Section: Methodsmentioning
confidence: 99%
“…Activity of GlpD was quantitated by determining the phenazine methosulfate (PMS)-coupled reduction of 2-(4,5-dimethyl-2-thiazolyl)-3,5-diphenyl-2H-tetrazolium bromide (MTT; ϭ 17 mM Ϫ1 ⅐cm Ϫ1 ); this reduction depends on glycerol-3-phosphate. The reaction is measured spectrophotometrically at 570 nm in the presence of 1% ␤-OG, as described (40). The ability of MD and HQNO to function as the electron-coupler in place of PMS was quantitated.…”
Section: Mapping Of ␤-Og and Lipid-interacting Surfaces By Means Of Lmentioning
confidence: 99%
“…Peptide surfactant must have the characteristic that similar to surfactant which can be used in crystalization, that is peptide surfactant must be designed to have hydrophylic residual and 3 -6 hydrophobic residual at the tail (Yeh et al 2005 peptide is designed to have 3 amino acid residual of hydrophobic, that is arginine (R), lysine (K) and aspargarine (N). Prediction of protein structure of 1x SUPEL peptide that fused with Thioredoxine and TEV is analyzed in silico with bioinformatics program.…”
Section: Discussionmentioning
confidence: 99%
“…These peptide surfactants represent a promising approach to membrane protein crystallization. V 6 D was used to solubilize the integral membrane protein glycerol 3-phosphate dehydrogenase in solution, when assayed through protein gel electrophoresis, retaining its functional enzymatic activities (38).…”
Section: Discussionmentioning
confidence: 99%